DETERMINANTS OF REPEATED ENDOWERS’ DONATION INTENTION IN CASH WAQF: A CASE STUDY IN MAJLIS AGAMA ISLAM DAN ADAT MELAYU PERAK (MAIPk) - Azizi, Nur Diyana; Shukor, Syadiyah Abdul; Sabri, Hisham (Jurnal Manajemen Bisnis, 2019)
Cash waqf means movable property which is structured by money and it is contributed for the waqf project development. To achieve this objective, committed endowers are needed to contribute continuously to ensure sufficient funds for waqf projects development in the future. Therefore, this study investigating the factors that determine the endowers’ intention to re-contribute to cash waqf by employing Extended Theory of Planned Behaviour (TPB). Data were collected through the survey questionnaires which is distributed to 374 endowers who are existing endowers. The result indicates that all variables predict the dependent variable. These results show that extended TPB is crucial in describing the repeated endowers’ donation intention in cash waqf. The result provide important insight for MAIPk to develope an effective marketing strategy to keep endowers contribute constantly in the future.